Optimizing silica encapsulation of living cells: in situ evaluation of cellular stress - Perullini, Ana Mercedes (2008)
The encapsulation of living cells in materials with good optical and mechanical properties often produces death or stress due to the release of toxic byproducts originated during the synthesis. We present here a method to assess the cellular stress that silica entrapment exerts over living cells taking into account the main preparation variables such as the nature of the silica source, protecting functional groups, total solid concentration, or indirect procedures. Measurement of the cellular stress status of genetically modified Sacharomyces cerevisiae, a true biological probe, allowed us to perform a quantitative analysis of cellular stress in a short time basis (compared to conventional long-term viability tests), opening the gate for a more sophisticated approach to optimize the synthesis conditions. In addition, the aforementioned findings allowed the preparation of novel materials with enhanced optical and mechanical properties. The relation of cellular stress with initial viability is also discussed. © 2008 American Chemical Society.